Advancing gynecologic surgery: vNOTES live surgery workshop debuts at Hospital Al-Sultan Abdullah - Abdullah, Bahiyah; Ahmad, Zatul Akmar; Idris, Suriani; Asmary, Asmahani; Daud, Suzanna; Wan Nordin, Nadzratulaiman (Faculty of Medicine, 2025)
On 10 July 2025, Hospital Al-Sultan Abdullah (HASA) hosted its first Live Surgery Workshop on vNOTES (vaginal Natural Orifice Transluminal Endoscopic Surgery), led by Assoc. Prof. Dr. Bahiyah Abdullah from the Department of Obstetrics & Gynaecology, Faculty of Medicine UiTM. This groundbreaking event marked an important milestone for HASA in advancing surgical education and innovation within the field of minimally invasive gynecologic surgery.